2008
DOI: 10.4049/jimmunol.180.9.5907
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-Specific T Cell Precursors with High Proliferative Capacity Correlate with Low Viremia and High CD4 Counts in Untreated Individuals

Abstract: Evidences have recently suggested that the preservation of vaccine-induced memory rather than effector T cells is essential for better outcome and survival following pathogenic SIV challenge in macaques. However, an equivalent demonstration in humans is missing, and the immune correlates of HIV-1 control have been only partially characterized. We focused on the quantification of Ag-specific T cell precursors with high proliferative capacity (PHPC) using a peptide-based cultured IFN-γ ELISPOT assay (PHPC assay)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…A number of studies have shown significant correlations between protective immunity and cultured ELISPOT responses (9,17,30,36). Although we have not shown definitively for cattle that the cultured ELISPOT assay measures only central memory, and not effector, T cell responses (due to a lack of specific reagents for central memory T cells in cattle, such as CCR7), a recent study revealed that PPD-specific cultured ELISPOT responses in humans were principally those of central memory T cells, as depletion of these cells ablated the cultured ELISPOT response (30).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown significant correlations between protective immunity and cultured ELISPOT responses (9,17,30,36). Although we have not shown definitively for cattle that the cultured ELISPOT assay measures only central memory, and not effector, T cell responses (due to a lack of specific reagents for central memory T cells in cattle, such as CCR7), a recent study revealed that PPD-specific cultured ELISPOT responses in humans were principally those of central memory T cells, as depletion of these cells ablated the cultured ELISPOT response (30).…”
Section: Discussionmentioning
confidence: 99%
“…In SIV-challenged RM, pathogenicity studies and vaccine trials have suggested that robust, multifunctional CD8 ϩ T-cell responses are correlated with a less-pathogenic course of infection (36,67). It is evident that the quantity and the quality of immune responses are critical for more-efficient containment of AIDS virus infections (9,40,67). The assays performed in the present study did not detect a qualitative difference in the cytokine pattern of the CD8 ϩ T-cell responses between the RM and vervet AGM chronically infected with SIV but did detect a lower number of responding CD8 ϩ T cells in the vervet AGM.…”
Section: Cd8mentioning
confidence: 99%
“…In a South African cohort of HIV-infected individuals, proliferation showed a significant inverse correlation with viral load, while cytokine production and degranulation did not (5). Ca-larota et al (2) recently also showed that the presence of antigen-specific T-cell precursors with high proliferative capacity was associated with HIV-1 control and preservation of CD4 counts. Additionally, T-cell proliferation has been associated with reduced HIV acquisition in Kenyan female sex workers (12).…”
Section: Hiv-specific Cd4mentioning
confidence: 93%